Impact of Work-Family Conflict and Overload on Turnover Intention: The Mediating Role of Job Stress in SOEs - Mualis, Rizky Septian; Shalahuddin, Ahmad; Irdhayanti, Efa; Daud, Ilzar; Marumpe, Dody Pratama (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The workforce represents a cornerstone for any organizations growth and long-term success, particularly amid the complexities of todays professional landscape. This reality also applies to Indonesias State-Owned Enterprises (SOEs) such as PT BRI, PT Pos Indonesia, PT Telkom Indonesia, Perum Bulog, and PT Pelindo. Employees within these institutions frequently struggle to strike a balance between professional responsibilities and personal life. The present study aims to explore how work-family conflict, workload pressure, and job-related stress influence the tendency of employees to consider leaving their jobs. Adopting a quantitative methodology, the study employed SmartPLS 4 for data analysis. Questionnaires were distributed to personnel across several SOEs, including the aforementioned companies. Findings revealed that both work-family tensions and high job demands significantly escalate employees turnover intention. Moreover, job stress emerged as a crucial intermediary factor that reinforces these effects. These insights underscore the importance for SOE leaders to implement supportive HR strategies that mitigate stress and foster healthier work-life integration. Addressing these issues not only reduces employee attrition but also contributes to stronger organizational stability and performance.